Antenatal Ultrasound Assessment of Intrauterine Growth Restriction in Pregnant Women - Mehwish Rasheed, Samra Zia, Azra Rashid, Asifa Majid, Bushra Sultana, Samina (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Intrauterine growth restriction (IUGR) is a major contributor to perinatal morbidity and mortality, often resulting from placental insufficiency, maternal conditions, or fetal abnormalities. Antenatal ultrasound and Doppler studies are essential for early detection, enabling timely intervention to improve outcomes. Objectives: To evaluate the role of antenatal ultrasound in the assessment of IUGR and to determine the association of abnormal umbilical artery Doppler findings with IUGR in pregnant women. Study Design & Setting: This descriptive cross-sectional study was conducted at the Department of Obstetrics and Gynecology Nishtar Hospital Multan over a period of six months. Methodology: A total of 150 pregnant women with singleton pregnancies, between 28–40 weeks of gestation, were included through consecutive sampling. Ultrasound was performed to record biparietal diameter (BPD), head circumference (HC), abdominal circumference (AC), femur length (FL), and estimated fetal weight (EFW). Doppler assessment of the umbilical artery was also conducted. IUGR was diagnosed when the EFW was below the 10th percentile for gestational age. Data were analyzed using SPSS, with p-values ≤0.05 considered statistically significant. Results: The mean maternal age was 28.45 ± 6.61 years and mean gestational age was 33.67 ± 3.76 weeks. IUGR was present in 15 (10.0%) women. EFW was significantly lower in the IUGR group compared to the non-IUGR group (2030.7 ± 146.7 g vs. 2815.8 ± 381.5 g, p < 0.001). No statistically significant association was found between IUGR and abnormal umbilical artery Doppler findings (p = 0.817). Conclusion: Antenatal ultrasound is a valuable tool for detecting IUGR, with EFW being the most sensitive parameter. Doppler assessment did not show a significant association with IUGR in this study. Keywords: abdominal circumference, biparietal diameter, Doppler, estimated fetal weight, femur length, intrauterine growth restriction, ultrasound, umbilical artery